Epigenetic basis of diabetic vasculopathy - Bhamidipati, Theja; Kumar, Manishekhar; Verma, Sumit S.; Mohanty, Sujit K.; Kacar, Sedat; Reese, Diamond; Martinez, Michelle M.; Kamocka, Malgorzata M.; Dunn, Kenneth W.; Sen, Chandan K.; Singh, Kanhaiya (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus (T2DM) causes peripheral vascular disease because of which several blood-borne factors, including vital nutrients fail to reach the affected tissue. Tissue epigenome is sensitive to chronic hyperglycemia and is known to cause pathogenesis of micro- and macrovascular complications. These vascular complications of T2DM may perpetuate the onset of organ dysfunction. The burden of diabetes is primarily because of a wide range of complications of which nonhealing diabetic ulcers represent a major component. Thus, it is imperative that current research help recognize more effective methods for the diagnosis and management of early vascular injuries. This review addresses the significance of epigenetic processes such as DNA methylation and histone modifications in the evolution of macrovascular and microvascular complications of T2DM.